De novo adrenal malignant peripheral nerve sheath tumor in a young female. An orphan disease - Ahluwalia, Rahul; Ahirwar, Hemant; Shukla, Archana; Tekam, Vijay; Lunawat, Aditya; Agrawal, Sudhanshu (International Surgery Journal, 2016)
Tumors arising from the adrenal gland are not uncommon. Most of these are benign diseases. Most malignancies of the adrenal gland are carcinomas and usually diagnosed at an advanced stage with a guarded prognosis. Malignant Peripheral Nerve Sheath Tumor (MPNST) of the adrenal gland is an extremely rare pathology, mostly seen amongst patients with Von Recklinghausen’s disease. Only eight cases of MPNST of the adrenal gland have been reported in the literature till date with only one case reported to be arising De Novo. Differentiation of this entity from other tumors of the adrenal gland becomes imperative in view of the various diagnostic and therapeutic implications. Moreover, the tumor size and pattern of expression for certain immunohistochemical markers may serve as independent predictors of aggressiveness. Herein we present the case of a 14 years old female who presented with a large right adrenal gland malignant peripheral nerve sheath tumor. With the nature of clinical presentation of this tumor, it is easy for the surgeon to be confused with any other adrenal tumor that tends to be benign. Differentiation of this entity from other soft tissue sarcomas and gastrointestinal stromal tumor of the adrenal gland becomes imperative in view of various diagnostic and therapeutic implications.